Fatigue of metals - Forrest, Peter George (Pergamon Press, 1970)
Fatigue of Metals provides a general account of the failure of metals due to fatigue, a subject of great practical importance in the field of engineering and metallurgy. The book covers a wide range of topics on the study of the fatigue of metals. The text presents in the first three chapters the characteristics and detection of fatigue fractures; methods of fatigue testing; and the fatigue strengths of different materials. The resistance of materials to fatigue under complex stress; the determination and effects of stress concentration; influence of surface treatment on fatigue strength; and.